Unveiling characteristic proteins for the structural development of beetle elytra. (1st March 2022) - Murata, Satoshi; Rivera, Jesus; Noh, Mi Yong; Hiyoshi, Naoya; Yang, Wen; Parkinson, Dilworth Y.; Barnard, Harold S.; Arakane, Yasuyuki; Kisailus, David; Arakaki, Atsushi
Abstract: Beetles possess a set of highly modified and tanned forewings, elytra, which are lightweight yet rigid and tough. Immediately after eclosion, the elytra are initially thin, pale and soft. However, they rapidly expand and subsequently become hardened and often dark, resulting from both pigmentation and sclerotization. Here, we identified changes in protein composition during the developmental processes of the elytra in the Japanese rhinoceros beetle, Trypoxylus dichotomus . Using mass spectrometry, a total of 414 proteins were identified from both untanned and tanned elytra, including 31 cuticular proteins (CPs), which constitute one of the major components of insect cuticles. Moreover, CPs containing Rebers and Riddiford motifs (CPR), the most abundant CP family, were separated into two groups based on their expression and amino acid sequences, such as a Gly-rich sequence region and Ala-Ala-Pro repeats. These protein groups may play crucial roles in elytra formation at different time points, likely including self-assembly of chitin nanofibers that control elytral macro and microstructures and dictate changes in other properties (i.e., mechanical property). Clarification of the protein functions will enhance the understanding of elytra formation and potentially benefit the development of lightweight materials for industrial and biomedical applications. Statement of significance: The beetle elytron is a light-weight natural bio-composite which displays high stiffness and toughness. This structure is composed of chitin fibrils and proteins, some of which are responsible for architectural development and hardening. This work, which involves insights from molecular biology and materials science, investigated changes in proteomic, architectural, and localized mechanical characteristics of elytra from the Japanese rhinoceros beetle to understand molecular mechanisms driving elytra development. In the present study, we identified a set of new protein groups which are likely related to the structural development of elytra and has potential for new pathways for processing green materials. Graphical abstract: Image, graphical abstract